2021
DOI: 10.1123/japa.2020-0211
|View full text |Cite
|
Sign up to set email alerts
|

Staying Strong Together: Older People Engaging in Resistance Training With a Peer

Abstract: The aim of this qualitative exploratory study was to investigate older adults’ perceptions of having a peer to encourage their participation in resistance training. The participants were recruited from a retirement village to undergo a 6-week resistance training program. Some participants attended a center; others participated in their home. Data were collected via semistructured interviews and analyzed thematically using a six-phase framework to obtain the participants’ perspectives about the peer support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A total of 36 studies were eligible for consideration comprising 16 peer support frameworks and volunteer guidelines and 15 peer reviewed studies supporting older community dwelling people (shown in Figure 1 ). Components from the following four peer support frameworks supporting older women were included in the backbone framework that was based on The Global Peer Support Framework and the National Volunteering Guidelines: Global peer for progress framework (Boothroyd & Fisher, 2010 ), Peer support mental health foundation (Shalaby & Agyapong, 2020 ), Peer support for resistance training among adults (Watkins et al, 2021 ), Healthcare peer support (Dennis, 2003 ). This led to the development of a draft peer volunteer framework to be used in Phase 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 36 studies were eligible for consideration comprising 16 peer support frameworks and volunteer guidelines and 15 peer reviewed studies supporting older community dwelling people (shown in Figure 1 ). Components from the following four peer support frameworks supporting older women were included in the backbone framework that was based on The Global Peer Support Framework and the National Volunteering Guidelines: Global peer for progress framework (Boothroyd & Fisher, 2010 ), Peer support mental health foundation (Shalaby & Agyapong, 2020 ), Peer support for resistance training among adults (Watkins et al, 2021 ), Healthcare peer support (Dennis, 2003 ). This led to the development of a draft peer volunteer framework to be used in Phase 2.…”
Section: Resultsmentioning
confidence: 99%
“…Peer support mental health foundation (Shalaby & Agyapong, 2020), 3. Peer support for resistance training among adults (Watkins et al, 2021), 4. Healthcare peer support (Dennis, 2003).…”
Section: Phase 1: Literature Search Review and Abstractionmentioning
confidence: 99%
“…Peers completed a 3 h training session prior to the RT participants commencing in their intervention programs. A full account of the peer training has been published previously [ 32 , 33 ]. The peer training included defining the peer and the peer role, presenting reasons why older adults participate or do not participate in RT (i.e., motivators and barriers), communicating with others, working as a team, and how to be a role model.…”
Section: Methodsmentioning
confidence: 99%
“…Experiences of being paired with a peer and interactions between the exercise participants and their peers have been published elsewhere [ 32 , 33 ]. These are not described in this article.…”
Section: Introductionmentioning
confidence: 99%